The Incidence of Onychomycosis Infection among Patients Referred to Hospitals in Kermanshah Province, Western Iran - Ali Mikaeili; Isaac Karimi (Tehran University of Medical Sciences, 2013)
Background: Onychomycosis is a nail disorder associated with aesthetic problems, discomfort, physical injury and loss of dexterity. The purpose of the present study was to isolate and identify the causative fungi of onychomycosis in 2402 patients in Kermanshah Province, western Iran in 1994 to 2010.Methods: Mycologic assessment was carried out by standard methods including either microscopic or cultural procedures.Results: Direct microscopy of the nail clips was positive in 1086 (45.2%) and fingernail and toenail onychomycoses were recognized in 773 (71.1%) and 313 (28.8%), respectively. Yeasts were detected in 853 (78.5%), dermatophytes in 201 (18.5%) and non-dermatophyte fungi in 32 (2.9%) patients. The results of fungal culture showed Candida albicans isolated in 384 (45.0%) and other Candida spp. isolated in 361 (54.0%) of the cases as the most common agents of onychomycosis while among dermatophytes, Trichophyton rubrum was found in 63 (37.0%) of the cases as the main dermatophytic agent followed by T. mentagrophytes 32 (15.9%) and Epidermophyton flocosum 30 (17.6%). Among the non-dermatophyte moulds, Aspergillus flavus was the most prevalent species 12 (37.5%) followed by A. niger 8 (25.0%) and A. fumigatus 4 (12.5%). Moreover, 139 (12.8%) samples with positive direct microscopy yielded no growth. The highest rate of onychomycosis was found in patients between 30-40 years of age.Conclusion: In sum, the current results identified the aetiological agents and primary epidemiological aspects of onychomycosis in west Iran.